Combination of Left Ventricular Noncompaction and Partial Atrioventricular Canal Defect in a 21-Year-Old Male: A Case Report. Issue 6 (January 2013) - Bodian, Malick; Jobe, Modou; Lèye, Mohamed; Ndiaye, Mouhamadou Bamba; Kane, Adama; Sarr, Simon Antoine; Mbaye, Alassane; Diao, Maboury; Ba, Fatimata Gatta; Ngaïdé, Aliou Alassane; Coly, Sarah Mouna; Thiam, Anna; et al.
Introduction: Left ventricular noncompaction (LVNC) is classified as a genetic cardiomyopathy characterized by a progressive systolic dysfunction. It may occur alone or in association with congenital cardiac anomalies. The combination of left ventricular noncompaction with partial atrioventricular canal defect is rare and has not, to our knowledge, been described previously. Case presentation: A 21-year-old male who traveled to our center from a neighboring country presented with signs of heart failure. Transthorarcic echocardiography showed prominent trabeculations in the left ventricle predominantly in the left ventricle involving the apical lateral and mid anterolateral segments associated with a partial atrioventricular canal defect. There was a biventricular systolic dysfunction. There was good response to medical treatment. Conclusion: This case stresses the importance of maintaining a high degree of suspicion for this rare cardiomyopathy and the need to systematically look for other associated anomalies in order to institute proper short- and long-term managements.